Oxygen reduction reaction on gold in alkaline solutions – The inner or outer sphere mechanisms in the light of recent achievements - Ignaczak, Anna; Santos, Elizabeth; Schmickler, Wolfgang (Current opinion in electrochemistry, 2019)
•Most recent findings about oxygen reduction on gold in alkaline media are reviewed.•Possibility of the oxygen molecule adsorption on various gold surfaces is discussed.•The effect of preadsorbed species on the oxygen adsorption on gold is stressed.•An outer sphere mechanism of electron transfer is postulated to be most probable. In this article we present a brief review of the latest publications on the problem of oxygen reduction reactions on gold in alkaline solutions. We focus mainly on the question whether this complex reaction proceeds according to the inner or outer sphere mechanism. Various aspects are discussed, such as an effect of the size, shape and surface characteristics of the metal on its activity towards the oxygen reduction, the strength of adsorption of oxygen molecule on gold, as well as the role of water and hydroxyl anions preadsorbed on the catalyst surface. It is shown that, despite the use of many research techniques and efforts of scientists, some aspects and details of mechanism of the oxygen reduction reaction on gold in alkaline solutions still remain unclear and are subject to scientific disputations. [Display omitted]